Characteristic Features of the Use of Information and Psychological Confrontation in the Middle East (Eurasian Journal of Humanities and Social Sciences, 2022)
This article discusses the characteristic features of the US information and psychological confrontation in Iraq and Russia in Syria, reflected in the conceptual and doctrinal documents during these armed conflicts.